Data flow analysis applied to optimize generic workflow problems - Matos, Paulo (2003)
The compiler process, the one that transforms a program in a high level language into assembly or binary code, is a much elaborated process that mixes several powerful technologies, some of them developed specifically for this area. Nowadays, compilers are highly developed systems that can analyze and improve quite efficiently the source code, profiting from all the potential of the new processor architectures. This paper introduces a common type of analysis - the Data Flow Analysis – that is used to compute flow-sensitive information about programs, whose results are essential to produce many code optimizations. It is also argued that the problem of analyzing the data flow in software programs has many similarities with the problems found in industrial engineering; planning and management. As consequence, it is possible to apply analysis and optimization techniques used by compilers in these areas.